The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/risa.13453
|View full text |Cite
|
Sign up to set email alerts
|

Work Conditions, Social Incorporations, and Foodborne Diseases Risk: Reflections About the (Non)Compliance of Food Safety Practices

Abstract: The number of foodborne diseases has increased in all continents, and efforts must be made to control this urgent and expressive public health problem. This article aims to present and discuss situations related to the compliance and noncompliance of food safety practices (FSPs) in light of Bourdieu's social theory. This qualitative study was conducted in commercial restaurants in two cities in São Paulo, Brazil. Participant observation was used in the restaurants, and notes referring to the kitchen workers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In addition, one of the dimensions of burnout, depersonalization [ 36 ] , can lead to detachment from customers, colleagues, and the work itself as a whole [ 95 ] , leading the employees to stop performing some critical activities because they feel it is no longer worth investing energy in them. In this case, food safety can be easily overlooked because it is not easily perceived by customers [ 96 ] and is not a priority for foodservice workers [ 18 ] . For example, a Chinese study on 453 restaurant chefs found a significant association between burnout and improper hand hygiene [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, one of the dimensions of burnout, depersonalization [ 36 ] , can lead to detachment from customers, colleagues, and the work itself as a whole [ 95 ] , leading the employees to stop performing some critical activities because they feel it is no longer worth investing energy in them. In this case, food safety can be easily overlooked because it is not easily perceived by customers [ 96 ] and is not a priority for foodservice workers [ 18 ] . For example, a Chinese study on 453 restaurant chefs found a significant association between burnout and improper hand hygiene [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, food safety behavior is a complex phenomenon. Food safety compliance is mainly seen as an additional requirement rather than a natural part of food handling, so it tends to be reactive rather than proactive [ 18 ]. In this case, burnout and work engagement may also play an essential role in food safety behavior.…”
Section: Model and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…49 In this study, we investigate the beliefs of employees for the priority of safety and expectations from the organization to perform the job safely. 50 Based on the above theoretical and empirical discussion, we propose the following hypotheses.…”
Section: Safety Compliance As a Mediator Between Safety Management An...mentioning
confidence: 99%
“…Disharmonic or non-motivating environments dehumanise workers and cause precarious working conditions since job satisfaction is insufficient, and they have poor infrastructure (i.e. lack of equipment, utensils, space to work, thermal comfort, insufficient number of employees and high noise levels), which can lead to pain and occupational diseases [36,37]. Furthermore, it is possible to find workers hurrying to meet the schedule for finishing the meals because of the lack of structure, which makes them more susceptible to errors, work accidents and the non-performance of steps essential to food safety.…”
Section: Kitchen Worker Subsystemmentioning
confidence: 99%